The impact of the COVID-19 pandemic on industrial policy in Germany and the European Union – the case of the automotive industry - Helena Gräf; Salome Topuria (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
The European Union (EU) and Germany were already being confronted with rapidly changing dynamics on the economic, ecological, and technological terrains prior to the Covid-19 crisis. The pandemic, however, has fully exposed critical global value chain (GVC) dependencies, jeopardising the already troubled automotive industry. By employing a historical-institutional and a pre- and post-Covid-19 industrial policy analysis, this article finds that, despite previous attempts, it was during the height of the pandemic that the implementation of green and digital industrial policy gained significant political support in Germany and the EU. In this context, there is an increased relevance of vertical industrial policy, which is geared towards the 'twin transition', partly altering the primarily horizontal industrial policy framework manifested in the post-Maastricht period.
Keywords: L5; L62; O38; 330; vertical industrial policy; automotive industry; Covid-19; geopoliticised competition; 'twin transition'